Learning Agenda on Gender and Climate Smart Agriculture: Evidence Summary - CGIAR GENDER Impact Platform (CGIAR GENDER Impact Platform, 2022)
This document provides a brief summary of the Evidence Resource Library (“library”) on Climate-Smart Agriculture (CSA) and gender equality as it relates to emerging learning gaps and questions for a Learning Agenda (LA) on the topic. The emerging learning gaps and questions described here represent the midpoint of the LA development process and are intended for discussion and refinement. It is not intended as an exhaustive review of resources in the library. A Systematic Review of literature on the topic has been commissioned and the report would be available in 2022.